Predisposing Factors for Granulomatous Lobular Mastitis: A Case-Control Study - Zeng Y; Zhang D; Zhao W; Fu N; Huang Q; Li S; Gao C; Yu J (Dove Medical Press, 2023)
Yifei Zeng,1,2 Dongxiao Zhang,1 Wenjie Zhao,1 Na Fu,1 Qiao Huang,1 Shuqi Li,2 Chang Gao,2 Jiale Yu2 1Department of Galactophore, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, Beijing, People's Republic of China; 2Graduate School, Beijing University of Chinese Medicine, Beijing, People's Republic of ChinaCorrespondence: Dongxiao Zhang, Department of Galactophore, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, No. 23, Art Museum Back Street, Dongcheng District, Beijing, People's Republic of China, Tel +86 13811077684, Email morningdong@163.comBackground: Despite the rising incidence rate of granulomatous lobular mastitis (GLM), uncertainties persist about its etiologic and predisposing factors to guide clinical treatment and early prevention. The objective of this study is to explore the predisposing factors for GLM.Patients and methods: This case-control study was conducted from 2018 to 2021 at Beijing Hospital of Traditional Chinese Medicine, Capital Medical University. Patients with GLM (cases) were matched with healthy examinees (controls) in a 1:1 ratio according to gender and living area. We analyzed their demographic features and investigated 75 factors that may be relevant to GLM using a standard questionnaire. Univariate and multivariable binary conditional logistic regression analyses were used to compare the differences between the two groups and evaluate the predisposing factors that may induce GLM.Results: There were 594 female GLM patients and 594 matched controls included in the study. The average age of the cases was 32.78 years (mainly 20 to 40). The incidence was high within five years after childbirth, and lesions were mainly in the unilateral breast. Univariate and multivariable conditional logistic regression analyses obtained six relevant factors and six high-risk factors. The six relevant factors included age, marriage, emotional abnormality, high prolactin, psychiatric drug intake, and sex hormone intake. Additionally, the independent high-risk factors for GLM included gestation, nipple invagination, blunt trauma, non-iatrogenic massage, lactation disorder, and nipple discharge (odds ratio (OR)=17.378, 8.518, 4.887, 3.116, 2.522, 1.685, P< 0.05). Menopause was an independent protective factor (OR=0.249, P< 0.05).Conclusion: The factors that increase milk and secretion production in the mammary duct are the main risk factors of GLM, especially when the nipples are invaginated. These factors can obstruct the duct and induce inflammation. Additionally, hormonal disorders, extrinsic trauma, and emotional abnormalities can accelerate the occurrence of GLM.Keywords: granulomatous lobular mastitis, GLM, predisposing factor, risk factor, case-control study, etiology